PERSPECTIVES REGARDING ANTENATAL CARE, DELIVERY AND BREAST FEEDING PRACTICES OF WOMEN FROM BALUCHISTAN, PAKISTAN - Khoso, Aneeta; Khan, Ayesha Zahid; Sayed, Sayeeda Amber; Rafique, Ghazala (Journal of Ayub Medical College Abbottabad, 2016)
Background: Antenatal Care is one of the fundamental rights for women to safeguard their health. Neonatal mortality rates have remained relatively static, compared to the decline in infant and under 5 mortality rates, adverse practices regarding breast feeding and pre-lacteal feeds being the important factors responsible. This study aimed to explore the Antenatal Care, delivery and breastfeeding practices in three districts of Baluchistan. Methods: It was a qualitative phenomenological design using Constructivist approach. The study was conducted in three districts of Baluchistan province, Gwadar, Quetta, Qila Saifullah. There were a total of 14 Focus Group Discussions with women regarding Antenatal Care, delivery and Breastfeeding practices, followed by audio taping, transcription as verbatim and analysis through Nvivo version 2. A process was deployed for identification and reporting of the components in order to ensure quality and validity of the qualitative findings. Results: Across the sites, women attended ANC at least once. However, their descriptions of ANC often varied. The women preferred Dais instead of doctors, due to the affordability, customs and availability. A lack of trained doctors and long distances to get a check-up lead to home deliveries in the study setting. Colostrum was discarded by majority of the mothers, while prelacteal feed was a common practice. Conclusion: This paper has explored factors affecting ANC attendance, delivery and breast feeding practices across three settings. Both the demand and supply side factors have an important influence on practices.